THE LIMITS OF THE EXTENDED HÜCKEL THEORY TO CALCULATE THE TOTAL DENSITY OF STATES OF MEDIUM-SIZED MOLECULES - GÓMEZ-JERIA,JUAN SEBASTIÁN (Sociedad Chilena de Química, 2006)
Two medium-sized molecular systems X60 (X=C,N) were analyzed using Extended Hückel, Density Functional and ab initio Hartree-Fock methods. The aim of the work was to test the reliability of the EHT methodology to calculate the total Density of States distribution curve. The Extended Hückel method is only reliable in the cases of the first valence and conduction bands of these systems. For the rest of the Density of States distribution curve EHT performs badly. The sources of error of EHT, come from the non-inclusion of the electron-electron interaction and from incorrect results regarding the relative ordering of the MO degeneracies. Both sources of error should disappear when the occupied and empty molecular orbitals become very similar in energy over a certain range, forming an almost continuous band, as happens in bigger molecular systems